"Reduce Food Waste, Save Money": Testing a Novel Intervention to Reduce Household Food Waste. Issue 2 (February 2021) - van der Werf, Paul; Seabrook, Jamie A.; Gilliland, Jason A.
An intervention, which used elements of the theory of planned behavior, was developed and tested in a randomized control trial (RCT) involving households in the city of London, Ontario, Canada. A bespoke methodology involving the direct collection and measurement of food waste within curbside garbage samples of control ( n = 58) and treatment households ( n = 54) was used to evaluate the effectiveness of the intervention. A comparison of garbage samples before and after the intervention revealed that total food waste in treatment households decreased by 31% after the intervention and the decrease was significantly greater ( p = .02) than for control households. Similarly, avoidable food waste decreased by 30% in treatment households and was also significantly greater ( p = .05) than for control households. Key determinants of treatment household avoidable food waste reduction included personal attitudes, perceived behavioral control, the number of people in a household, and the amount of garbage set out.